Complementary Feeding: A Position Paper by the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) Committee on Nutrition. Issue 1 (January 2017) - Fewtrell, Mary; Bronsky, Jiri; Campoy, Cristina; Domellöf, Magnus; Embleton, Nicholas; Fidler Mis, Nataša; Hojsak, Iva; Hulst, Jessie M.; Indrio, Flavia; Lapillonne, Alexandre; Molgaard, Christian
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: This position paper considers different aspects of complementary feeding (CF), focussing on healthy term infants in Europe. After reviewing current knowledge and practices, we have formulated these recommendations: Timing : Exclusive or full breast-feeding should be promoted for at least 4 months (17 weeks, beginning of the 5th month of life) and exclusive or predominant breast-feeding for approximately 6 months (26 weeks, beginning of the 7th month) is a desirable goal. Complementary foods (solids and liquids other than breast milk or infant formula) should not be introduced before 4 months but should not be delayed beyond 6 months. Content: Infants should be offered foods with a variety of flavours and textures including bitter tasting green vegetables. Continued breast-feeding is recommended alongside CF. Whole cows' milk should not be used as the main drink before 12 months of age. Allergenic foods may be introduced when CF is commenced any time after 4 months. Infants at high risk of peanut allergy (those with severe eczema, egg allergy, or both) should have peanut introduced between 4 and 11 months, following evaluation by an appropriately trained specialist. Gluten may be introduced between 4 and 12 months, but consumption of large quantities should be avoided during the first weeks after gluten introduction and later during infancy. All infants should receive iron-rich CF including meat products and/or iron-fortified foods. No sugar or salt should be added to CF and fruit juices or sugar-sweetened beverages should be avoided. Vegan diets should only be used under appropriate medical or dietetic supervision and parents should understand the serious consequences of failing to follow advice regarding supplementation of the diet. Method: Parents should be encouraged to respond to their infant's hunger and satiety queues and to avoid feeding to comfort or as a reward.